Language Activism Imaginaries and Strategies of Minority Language Equality - De Korne, Haley (Contributions to the Sociology of Language [CSL], 2021)
Through an ethnographic account of Isthmus Zapotec language advocates in Oaxaca, Mexico, this study illuminates a repertoire of advocacy strategies that are bringing linguistic equality closer to reality.